Background Papers Written for the Economic and Planning Council for Karnataka Volume II - Planning Commission (Planning Commission, 1984)
Karnataka forms the South-Western part of the Deccan Peninsula and lies between 11°.5' and 18°.6' north latitudes and 74°.O' and 78°.4' east longitudes, witty an area of 1,51,773 sq.kms. The population of the State as per the 1981 census was 37.04 million consisting of a rural, population of 26.33 millions and an urban population of 10.71 million. It is expected to increase to 58,9 millions consisting of a rural population of 35.1 millions and urban population of 23.8 millions in 2001 AD.
Agriculture Forestry Irrigation